Preparation of a graphene oxide membrane for air purification - Weiwu Zou; Baoshan Gu; Shiqing Sun; Shidong Wang; Xin Li; Haoqi Zhao; Peiyan Yang (Materials Research Express, 2019)
Environmental issues such as particulate matter (PM) have become more and more serious because of their detrimental effects on human health. The development of an effective way to remove PM is in high demand. In this study, a graphene oxide (GO) membrane with a large specific surface area and a continuous pore structure was prepared via a coating method. The morphology, composition and structure of the GO membrane were characterized by scanning electron microscopy (SEM), an energy dispersive spectrometer (EDS), X-ray diffraction (XRD), FT-IR spectra, X-ray photoelectron spectra (XPS) and Raman spectroscopy. The removal efficiency for PM and the influence of pollutant concentration and wind velocity on the GO membrane were studied. As a result, when the wind velocity was 0.1 m s ^−1 , the PM _2.5 removal efficiency of the GO membrane exhibited the highest efficiency (99.46%) with a low pressure drop (7 Pa) and a high quality factor (QF) of 0.75 Pa ^−1 . The GO membrane maintained a high adsorption performance for a long time. The GO membrane removal efficiency was more significant when the import concentration was higher and the wind velocity was lower. In particular, SEM and EDS clearly revealed that the PM _2.5 was successfully captured by the GO membrane. The preparation of the GO membrane involves a simple and pollution-free process, which provides a new way to deal with air pollution.